Technical Skill Development for Vocational High School Students through Practical Training in Geodetic GPS Instrumentation - Taufiq Natsir; Ridwan Ridwan; Ishak Ishak; Ramli Rasyid (PT. Global Research Collaboration, 2025)
Training on the Use of Geodetic GPS is a form of community service aimed at enhancing the technical competencies of vocational high school students in the field of surveying and mapping. Amid the rapid advancement of geospatial technologies, vocational schools face significant challenges in providing training based on modern equipment, resulting in a skills gap between graduates’ competencies and industry demands. This initiative was motivated by the low proficiency of students in operating modern geospatial measurement tools, which are increasingly essential in the professional field. The community service activity was conducted in partnership with SMK Negeri 1 Takalar, targeting 11th and 12th grade students of the Building Information Design and Modeling (DPIB) program. The training employed an experiential learning approach, consisting of concise theoretical instruction, field practice, and a mini-project involving the creation of maps using GPS-based data. A pre-post test evaluation method was explicitly used to assess improvements in students’ knowledge and skills before and after the training. The results showed a significant increase in the understanding of basic GNSS concepts and in students' abilities to collect and process coordinate data. Post-test scores improved by 63% compared to pre-test results, and all student groups successfully completed an independent simple mapping project. This activity also boosted students’ confidence and had a positive impact on their job readiness. The results indicate that hands-on training is highly effective in bridging the competency gap between vocational education and industry requirements, and that this approach should be further developed through a more comprehensive series of training programs.